PRAKTIK PENDIDIKAN MANAJEMEN KEBERSIHAN MENSTRUASI SISWI SMP/MTs - Wahida Yuliana; Retno Hastri RR; Agustina Widayati (Rena Cipta Mandiri, 2025)
Pure and healthy living behaviors must be instilled from an early age, including menstrual hygiene management (MHM), which should be introduced to adolescent girls from a young age, even before they menstruate. This activity will provide many positive benefits in the future. The purpose of this study was to evaluate the practice of reproductive education related to menstrual hygiene management among middle school adolescents in the Zainul Hasan Islamic Boarding School environment, Probolinggo Regency. A cross-sectional study was conducted with a sample of 198 female adolescent students selected using stratified random sampling method. Data were collected using a questionnaire in the form of a Google form distributed online; after data processing, it was continued with descriptive analysis with SPSS version 26. The results showed that 45% of middle school students had good knowledge about maintaining hygiene during menstruation. 62% of those with good knowledge obtained MHM information from school and 25% from family. The average age of participants was 14 years (SD = 0.8). Research findings show that there are middle school students who have low levels of MHM knowledge and this makes it important for schools to collaborate with midwives to continuously provide MHM education to adolescents in addition to other health education as a form of behavioral intervention.